Design and Implementation of the University of Maryland Keck Laboratory for the Analysis of Visual Movement - Cutler, Ross; Duraiswami, Ramani; Hench Qian, J.; S. Davis, Larry (2002)
The Keck Laboratory for the Analysis of Vision Motion is a state-of-the art multi-perspective imaging laboratory recently established at the University of Maryland. In this paper, we describe the design and architecture of the lab, that is currently being used to support many computer vision studies. In particular, we discuss: camera synchronization, image resolution analysis, image noise analysis, stereo error analysis, video capture, lighting, calibration hardware.